Frontal QRS-T angle in scorpion sting - Yasak, İbrahim Halil; Yılmaz, Mustafa (Acil Tıp Uzmanları Derneği, 2022)
Introduction: The aim of this study was to investigate the change in frontal QRS-T angle in different clinical stages of scorpion stings. Materials-Method: In this retrospective study, laboratory data of patients and T angle, QRS duration (ms), QT duration (ms), and QTc duration (ms) of the patients who presented with scorpion sting were calculated and recorded in the data file. The results were analyzed. Findings: Eighty patients who applied to the emergency department with the complaint of scorpion sting were included in our study. Forty-four patients were evaluated as Stage I, 26 as Stage II, and 10 as Stage III. The patient groups did not differ in age (p = 0.605) and sex (p = 0.432). No significant difference was observed between the laboratory findings of the patients at the time of admission. ECG findings showed a considerable difference in frontal QRS-T angles between scorpion sting stages (p < 0.001). Pairwise comparison of the stages with post-hoc analysis revealed a non-significant difference between Stages I and II (p = 0.143), and a significant difference between Stages I and III (p < 0.001) and Stages II and III (p = 0.003). Correlation analysis results showed that the frontal QRS-T angle was negatively correlated with age (r = ?0.281, p = 0.016) and positively correlated with the clinical stage (r = 0.384, p = 0.001). Multivariate linear regression analysis was performed to identify independent predictors of frontal QRS-T angle, and the stage of the scorpion sting was identified as an independent predictor (p = 0.001). Conclusion: The increase in frontal QRS-T angle in scorpion stings may be used as a parameter that can help both early detections of cardiac involvement and clinical staging

Giriş: Bu çalışmanın amacı, akrep sokmalarının farklı klinik evrelerinde frontal QRS-T açısındaki değişimi araştırmaktır. Gereç-Yöntem: Bu retrospektif çalışmada akrep sokması ile başvuran hastaların laboratuvar verileri ile T açısı, QRS süresi (ms), QT süresi (ms), QTc süresi (ms) hesaplanarak veri dosyasına kaydedilmiştir. Sonuçlar analiz edilmiştir. Bulgular: Çalışmamıza akrep sokması şikayeti ile acil servise başvuran 80 hasta dahil edildi. Hastaların 44'ü Evre I, 26'sı Evre II ve 10'u Evre III olarak değerlendirildi. Hasta grupları arasında yaş (p=0.605) ve cinsiyet (p=0.432) açısından fark yoktu. Hastaların başvuru anındaki laboratuvar bulguları arasında anlamlı fark izlenmedi. Elektrokardiyografi (EKG) bulguları, akrep sokması evreleri arasında frontal QRS-T açılarında anlamlı farklılık gösterdi (p < 0.001). Evremelerin post-hoc analiz ile ikili olarak karşılaştırılması, Evre I ve II (p = 0.143) arasında anlamlı bir fark olmazken ve Evre I ve III (p 0.001) ile Evre II ve III (p = 0.003) arasında anlamlı bir fark ortaya koymuştur. Korelasyon analizi sonuçları, frontal QRS-T açısının yaş ile negatif (r = ?0.281, p = 0.016) ve klinik evre ile pozitif korelasyon (r = 0.384, p = 0.001) olduğunu gösterdi. Frontal QRS-T açısının bağımsız belirleyicilerini belirlemek için çok değişkenli doğrusal regresyon analizi yapıldı ve akrep sokmasının evresi bağımsız bir belirleyici olarak belirlendi (p = 0.001). Sonuç: Akrep sokmalarında frontal QRS-T açısındaki artış hem kardiyak tutulumun erken saptanmasına hem de klinik evrelemeye yardımcı olabilecek bir parametre olarak kullanılabilir.
Akrep sokmasında frontal QRS-T açısı
Keywords: Toxicology; Toksikoloji